2010
DOI: 10.5194/acp-10-6947-2010
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of transported background ozone on California air quality during the ARCTAS-CARB period – a multi-scale modeling study

Abstract: Abstract. Multi-scale tracer and full-chemistry simulations with the STEM atmospheric chemistry model are used to analyze the effects of transported background ozone (O 3 ) from the eastern Pacific on California air quality during the ARCTAS-CARB experiment conducted in June, 2008. Previous work has focused on the importance of long-range transport of O 3 to North America air quality in springtime. However during this summer experiment the longrange transport of O 3 is also shown to be important. Simulated an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 32 publications
3
84
0
Order By: Relevance
“…In their study of aircraft data from the CalNex 2010 experiment, Nowak et al (2012) found that ammonia emissions from dairy facilities in Southern California have a significant effect on nitrate aerosol formation, shifting the NH 4 NO 3 equilibrium towards the particle phase and resulting in higher nitrate aerosol concentrations downwind of the dairy facilities. They also compared the CalNex aircraft data to NEI 2005 and CARB-ARCTAS 08 (Huang et al, 2010) emissions inventories of ammonia in the South Coast Air Basin and found that both emissions inventories underestimate ammonia emissions relative to emissions estimates derived from the aircraft data. In the NEI 2005 inventory, which is used in GEOS-Chem, ammonia emissions from automobiles and dairy facilities in this region are 38 and 1 metric tonnes per day, respectively, compared to 56 and 11 tonnes per day, respectively, in the CARB-ARCTAS 08 inventory.…”
Section: Nitrate Under-prediction In Californiamentioning
confidence: 99%
“…In their study of aircraft data from the CalNex 2010 experiment, Nowak et al (2012) found that ammonia emissions from dairy facilities in Southern California have a significant effect on nitrate aerosol formation, shifting the NH 4 NO 3 equilibrium towards the particle phase and resulting in higher nitrate aerosol concentrations downwind of the dairy facilities. They also compared the CalNex aircraft data to NEI 2005 and CARB-ARCTAS 08 (Huang et al, 2010) emissions inventories of ammonia in the South Coast Air Basin and found that both emissions inventories underestimate ammonia emissions relative to emissions estimates derived from the aircraft data. In the NEI 2005 inventory, which is used in GEOS-Chem, ammonia emissions from automobiles and dairy facilities in this region are 38 and 1 metric tonnes per day, respectively, compared to 56 and 11 tonnes per day, respectively, in the CARB-ARCTAS 08 inventory.…”
Section: Nitrate Under-prediction In Californiamentioning
confidence: 99%
“…Further improvements are therefore needed in the observing systems that provide information on the three-dimensional pollutant concentrations. For example, such improvements are needed to better quantify the long-range pollutant transport of Saharan dust to Southern Europe and Asian brown dust cloud to the US West Coast (Huang et al, 2010).…”
Section: Boundary Conditions and Nesting Of Cwf Modelsmentioning
confidence: 99%
“…In reality, background CO mixing ratios are likely to vary in time as a result of long-range transport from Asia (e.g. Jaffe et al, 1999;Huang et al, 2010). WRF-Chem was not coupled with a global model prediction system since the primary purpose was to predict plume locations to guide aircraft operations rather than simulate exact magnitudes.…”
Section: Operational Forecastingmentioning
confidence: 99%
“…Seaman et al, 1995;Dabub et al, 1999;Jacobson, 2001;Bao et al, 2008;Jin et al, 2010;Huang et al, 2010;Michelson et al, 2010;Pfister et al, 2011) have improved the understanding of how meteorological processes in California affect the spatial variations and chemical transformation of pollutants. Various routine measurements and several special studies in the Central Valley of California have shown that pollutants emitted from Sacramento, California during the summer are frequently transported by the thermally-driven upslope flows that draw the urban air towards the northeast over the foothills of the Sierra Nevada (Murphy et al, 2006).…”
Section: Introductionmentioning
confidence: 99%